Emotions and Economic Theory - Elster, Jon (Journal of Economic Literature, 1998)
Economists and psychologists who study emotions have worked in near-total isolation from each other. The article discusses some areas in which economists might take account of emotions. After a survey of the main features of emotions as analyzed by psychologists and physiologists, the article discusses three aspects of the relation between emotion and choice. (1) Given that emotions may be intrinsically valuable or instrumentally useful, can one choose to have them? (2) Can emotions supplement rationality in cases where it yields indeterminate prescriptions for choice? (3) When an emotion and self-interest suggest different courses of action, how do they interact to produce a final decision?